Українські етнічні ознаки як чинник соціального прогресу в доктрині М. Драгоманова - Собчук, Володимир; Sobchuk, Volodymyr (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено внесок М. Драгоманова у дослідження ролі мови і традиційної культури як засобів збереження ідентичності українського етносу та підтримки стабільності соціальної структури. Розкрито його ставлення до мовно-культурної уніфікації у націогенезі.

M. Dragomanov insisted that belonging to the ethnos is a way of joining with common to all mankind values. He observed that the ethnic features perform the functions of the social stabilization and the means of the national consolidation. They promote the forming of the common communicative space within the bounds of the nation. The scientist proved that the language and the traditional culture evolve under the influence of the historical and geographical factors. They are the connecting link between the past and the future. The scientist supposed that the moral degradation of the society can become the result of their lass. He was sure that the national language and the traditional culture must not be subject of the political system. M. Dragomanov was the first in the Ukrainian social and political conception to offer the acceptance of the ethnic features from the scientific point of view: to learn their functions in the life of the nation without the exaggeration of their meaning as a symbol in the process of the «national renewal».
Ukrainian ethnicity as a factor of social progress in the doctrine M. Drahomanov
Keywords: нація; етнос; мова; традиційна культура; асиміляція; nation; ethnos; language; traditional culture; assimilation